Childhood acquired cholecystopathies: About 2 cases - Etcheverría Prieto, Pedro M. (Cirugía del Uruguay, 1975)
The authors report 2 cases of acquired gall bladder diseases in 5 and 12 year-old children. One of them had a cholelithiasis set on a cholesteiolosis. The other who had been cholecystostomysed during the post-natal period under the suspicion of biliary duct malformation, had a solitary stone, centered upon a suture material. The calculus occluded the gall bladder cervix intermitently, thus determining acute distentions of the cholecyst.